Teacher Advocacy for Gamified Digital Learning Laboratories: A Qualitative Analysis of Positive Perceptions and Enhancement Strategies for English Language Teaching in Indonesia - Mochamad Nasrul Chotib; Yazid Basthomi; Falentinus Ndruru; Mala Rovikasari; Suhono; Rurik Herawati; Dina Marita; Dino Sugiarto (CV. Creative Tugu Pena, 2025)
In the context of English language teaching (ELT) in Indonesia, understanding teacher perceptions is crucial for successful implementation. This study aims to explore the positive perceptions of Indonesian elementary and junior high school teachers regarding Platform Digital Pembelajaran Bahasa Inggris (PDPBI), Digital Learning Laboratories (DLL), and gamified DLLs, and to synthesize their constructive suggestions for system enhancement. A qualitative need analysis was conducted via a structured questionnaire with five teachers. Data were analyzed thematically to identify key themes related to benefits and proposed modifications. Teachers perceive these platforms as significant tools for enhancing flexibility, student motivation, interactivity, and differentiated learning. Their advocacy is not uncritical; they provide nuanced recommendations for improving features (intuitive UI/UX, better audio-visuals), content (curriculum-aligned, relevant), exercise genres (varied and HOTS-inclusive), and gamification mechanics (educative rewards, healthy ranking systems, contributor recognition for teachers). The findings suggest that Indonesian teachers are proactive advocates for gamified DLLs. Their insights provide a valuable framework for developers and policymakers to create more effective, engaging, and pedagogically sound digital learning environments that are supported by their primary users—the teachers themselves